The harp of prophecy : early Christian interpretation of the Psalms - Daley, Brian E.; Kolbet, Paul R. (Christianity and Judaism in antiquity, 2015)
The Psalms generated more biblical commentary from early Christians than any other book of the Hebrew and Christian canon. While advances have been made in our understanding of the early Christian preoccupation with this book and the traditions employed to interpret it, no study on the Psalms traditions exists that can serve as a solid academic point of entry into the field. This collection of essays by distinguished patristic and biblical scholars fills this lacuna. It not only introduces readers to the main primary sources but also addresses the unavoidable interpretive issues present in the secondary literature. The essays in The Harp of Prophecy represent some of the very best scholarly approaches to the study of early Christian exegesis, bringing new interpretations to bear on the work of influential early Christian authorities such as Athanasius, Augustine, and Basil of Caesarea. Subjects that receive detailed study include the dynamics of early Christian political power, gender expressions, and the ancient conversation between Christian, Jewish, and Greek philosophical traditions. The essays and bibliographic materials enable readers to locate and read the early Christian sources for themselves and also serve to introduce the various interdisciplinary methods and perspectives that are currently brought to bear on early Christian psalm exegesis. Students and scholars of theology and biblical studies will be led in new directions of thought and interpretation by these innovative studies. --